Exemplar and Educational Preference: The Influence of Religious Figures on Interest in Islamic Education in Indonesia - Zubaidi, Ahmad; Zerrouki, Taha (Universitas Islam Indonesia, 2024)
This current research aims to analyse the influence of religious figures on people's interest in choosing Islamic education in the Indonesian context. This study involved 400 respondents from various regions. From the data collected through the survey method, results show that people's perceptions of religious figures significantly influence their interest in choosing an Islamic educational institution. As many as 75% of respondents considered religious figures before deciding to send their child to an Islamic school. This research also revealed that trust in religious figures with a good reputation can increase people's satisfaction with Islamic education. In addition, there is tension between tradition and modernity in Islamic education, which indicates the need to modernize the curriculum to remain relevant to global developments. It is hoped that these findings can be a guide for policymakers in formulating strategies to increase the interest and quality of Islamic education in Indonesia.